2006
DOI: 10.7326/0003-4819-145-12-200612190-00144
|View full text |Cite
|
Sign up to set email alerts
|

Literacy and Misunderstanding Prescription Drug Labels

Abstract: Lower literacy and a greater number of prescription medications were independently associated with misunderstanding the instructions on prescription medication labels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
453
4
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 551 publications
(473 citation statements)
references
References 30 publications
11
453
4
5
Order By: Relevance
“…This criticism can also be directed at many seminal health literacy studies that have examined associations with the ability to perform common self-management tasks. 4,[57][58][59] In fact, assessments of health literacy closely resemble cognitive tests, supporting the primary assertion of the LitCog study. The most notable similarity can be seen between the REALM and the American-National Adult Reading Test (AM-NART); both require individuals to correctly pronounce lists of words (r= 0.73).…”
Section: Discussionmentioning
confidence: 66%
“…This criticism can also be directed at many seminal health literacy studies that have examined associations with the ability to perform common self-management tasks. 4,[57][58][59] In fact, assessments of health literacy closely resemble cognitive tests, supporting the primary assertion of the LitCog study. The most notable similarity can be seen between the REALM and the American-National Adult Reading Test (AM-NART); both require individuals to correctly pronounce lists of words (r= 0.73).…”
Section: Discussionmentioning
confidence: 66%
“…Prior research examining medication misunderstanding, use and non-adherence to prescription and non-prescription drugs have reported similar findings. [23][24][25][26] Our study provides additional evidence of the problem of confusing OTC medication labeling, especially for the large proportion of Americans who have inadequate health literacy skills. Interestingly, we also found that one in five adults in our sample self-reported heavy acetaminophen use over the past six months.…”
Section: Discussionmentioning
confidence: 81%
“…In calculating the ROC curve for each possible cut point of the MMSE (25)(26)(27)(28)(29), the greatest area under the ROC curve for the TOFHLA, REALM and NVS was 0.84, 0.86, and 0.82 respectively (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…1 While a 'universal precautions' approach for using clear health communication practices has been recommended by the American Medical Association, 25 some studies have shown that simply using plain language and 'teach back' methods to confirm understanding may not be sufficient. 26 Therefore, creating, identifying, and validating rapid assessment tools that measure health literacy for clinical purposes has become of increasing interest. Currently, routinely collected patient information cannot adequately identify those with limited health literacy.…”
Section: Discussionmentioning
confidence: 99%